The anatomy of loneliness : suicide, social connection, and the search for relational meaning in contemporary Japan - Ozawa-de Silva, Chikako, 1970- (Ethnographic studies in subjectivity, 2021)
"Loneliness is everybody's business. Neither a pathology, nor a rare affliction, it is part of the human condition. Severe and chronic loneliness, however, is a threat to individual and public health and appears to be on the rise. In this illuminating book, anthropologist Chikako Ozawa-de Silva examines loneliness in Japan, focusing on rising rates of suicide, the commodification of intimacy, and problems impacting youth. Moving from interviews with college students, to stories of isolation following the 2011 natural and nuclear disasters, to online discussions in suicide website chat rooms, Ozawa-de Silva points to how society itself can exacerbate experiences of loneliness. A critical work for our world, The Anatomy of Loneliness considers how to turn the tide of the "lonely society" and calls for a deeper understanding of empathy and subjective experience on both individual and systemic levels"--